Transcriptome analysis of the fungal pathogen Fusarium oxysporum f. sp. medicaginis during colonisation of resistant and susceptible Medicago truncatula hosts identifies differential pathogenicity profiles and novel candidate effectors - Thatcher, L.; Williams, A.; Garg, G.; Buck, S.; Singh, Karam (Biomed Central Ltd, 2016)
Background: Pathogenic members of the Fusarium oxysporum species complex are responsible for vascular wilt disease on many important crops including legumes, where they can be one of the most destructive disease causing necrotrophic fungi. We previously developed a model legume-infecting pathosystem based on the reference legume Medicago truncatula and a pathogenic F. oxysporum forma specialis (f. sp.) medicaginis (Fom). To dissect the molecular pathogenicity arsenal used by this root-infecting pathogen, we sequenced its transcriptome during infection of a susceptible and resistant host accession. Results: High coverage RNA-Seq of Fom infected root samples harvested from susceptible (DZA315) or resistant (A17) M. truncatula seedlings at early or later stages of infection (2 or 7 days post infection (dpi)) and from vegetative (in vitro) samples facilitated the identification of unique and overlapping sets of in planta differentially expressed genes. This included enrichment, particularly in DZA315 in planta up-regulated datasets, for proteins associated with sugar, protein and plant cell wall metabolism, membrane transport, nutrient uptake and oxidative processes. Genes encoding effector-like proteins were identified, including homologues of the F. oxysporum f. sp. lycopersici Secreted In Xylem (SIX) proteins, and several novel candidate effectors based on predicted secretion, small protein size and high in-planta induced expression. The majority of the effector candidates contain no known protein domains but do share high similarity to predicted proteins predominantly from other F. oxysporum ff. spp. as well as other Fusaria (F. solani, F. fujikori, F. verticilloides, F. graminearum and F. pseudograminearum), and from another wilt pathogen of the same class, a Verticillium species. Overall, this suggests these novel effector candidates may play important roles in Fusaria and wilt pathogen virulence. Conclusion: Combining high coverage in planta RNA-Seq with knowledge of fungal pathogenicity protein features facilitated the identification of differentially expressed pathogenicity associated genes and novel effector candidates expressed during infection of a resistant or susceptible M. truncatula host. The knowledge from this first in depth in planta transcriptome sequencing of any F. oxysporum ff. spp. pathogenic on legumes will facilitate the dissection of Fusarium wilt pathogenicity mechanisms on many important legume crops.